Applications of Discrete Synthetic Macromolecules in Life and Materials Science: Recent and Future Trends. Issue 6 (25th January 2021) - Aksakal, Resat; Mertens, Chiel; Soete, Matthieu; Badi, Nezha; Du Prez, Filip
Abstract: In the last decade, the field of sequence‐defined polymers and related ultraprecise, monodisperse synthetic macromolecules has grown exponentially. In the early stage, mainly articles or reviews dedicated to the development of synthetic routes toward their preparation have been published. Nowadays, those synthetic methodologies, combined with the elucidation of the structure–property relationships, allow envisioning many promising applications. Consequently, in the past 3 years, application‐oriented papers based on discrete synthetic macromolecules emerged. Hence, material science applications such as macromolecular data storage and encryption, self‐assembly of discrete structures and foldamers have been the object of many fascinating studies. Moreover, in the area of life sciences, such structures have also been the focus of numerous research studies. Here, it is aimed to highlight these recent applications and to give the reader a critical overview of the future trends in this area of research. Abstract : A comprehensive overview of the applications of discrete synthetic macromolecules in biology and materials science is presented. Topics as diverse as macromolecular data storage, self‐assembly, foldamers, catalysis, lectin‐binding, and antimicrobial properties are presented. Additionally, features such as the influence of sequence regulation on the physical properties of such uniform macromolecules are elaborated and future trends in the field are provided.